Synthesis of Tetra‐Substituted Trifluoromethyl‐3, 1‐Benzoxazines by Transition‐Metal‐Catalyzed Decarboxylative Cyclization of N‐Benzoyl Benzoxazinones. Issue 5 (4th May 2021) - Uno, Hiroto; Fujimoto, Daichi; Harada, Kyosuke; Tanaka, Chika; Shibata, Norio
Abstract: Invited for this month's cover are the group of Norio Shibata at Nagoya Institute of Technology (Japan). The cover picture is inspired by the diversity in the ocean also in cyberspace. In the present research, we can synthesize diverse heterocyclic molecules having a trifluoromethyl group in a single step by changing the N ‐substitution. You can see more variations of trifluoromethyl heterocycles in several papers by our group. Read the full text of their Communication at 10.1002/open.202000360 . Abstract : "… The cover image is inspired by the diversity in the ocean also in cyberspace…" Find out more about the story behind the front cover research at 10.1002/open.202000360 .